(untitled) (Journal of responsible AI & ethics, 2026)
Artificial Intelligence (AI) has emerged as a transformative technology with the potential to revolutionize healthcare systems worldwide, especially in addressing the persistent issue of global health equity. Despite advancements in healthcare, disparities in access to quality medical services, particularly in low- and middle-income countries, continue to exacerbate health outcomes and create significant barriers to achieving universal health coverage. AI presents a unique opportunity to bridge these gaps by providing innovative solutions to improve healthcare accessibility, affordability, and quality. This paper explores the role of AI in enhancing global health equity, focusing on its diverse applications across healthcare systems, from diagnostics and predictive analytics to telemedicine and personalized medicine. Through the integration of AI technologies, healthcare delivery in underserved regions can be significantly enhanced, ensuring more timely interventions and reducing the burden on existing healthcare infrastructures. By examining case studies from regions such as rural India, Sub-Saharan Africa, and Southeast Asia, this study demonstrates how AI-driven tools are being employed to diagnose diseases, predict health trends, and optimize resource distribution, leading to better health outcomes for underserved populations. Furthermore, this paper delves into the ethical implications of AI in healthcare, such as concerns about data privacy, algorithmic biases, and the potential for reinforcing existing disparities. While AI offers promising opportunities, it also presents challenges that need to be addressed to ensure equitable outcomes. The paper also highlights the need for policies that prioritize transparency, accountability, and inclusivity in AI systems, to mitigate risks and ensure fair distribution of the benefits across diverse populations.